La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Jumol-Julia Edéry’s Wedding in Early 20th Century Morocco - Cohen, Judith R. (Canadian Jewish Studies/Études juives canadiennes, 2022)

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

Bïa Krieger versionista: Três cançoes de Chico Buarque em francês [Bïa Krieger, versionista. Trois chansons de Chico Buarque en français] - Cassiano, Raissa Conde (Université de São Paulo, 2020)

L'adaptation de chanson dans l'album ”Cœur vagabond” de Bïa. Une brise de Brésil - Abbrugiati, Perle (ATeM – Archiv für Textmusikforschung, 2019)
Perle Abbrugiati's article explores Coeur vagabond/Coraçao vagabundo, the fourth record by the French-Brazilian artist Bïa, released in 2006. The bilingual album comprises an equal number of Brazilian-Portuguese adaptations from French songs and French adaptations from Brazilian songs. The aim of the present article is to identify the strategies applied in the translation of songs. To this end, the article's author herself uses translation within the framework of a comparative approach, confronting Bïa's translations with her own literal translations (not suitable to be sung) of the original lyrics. The objective is not to trace 'mistranslations' but to point out in how many different and intricate ways a translation can be faithful while being creative, and in what way and to what degree the song translator may take the liberty of 're-semantisation'.
Keywords: Chanson; traduction

“Portrait en Noir et Blanc”: Chico Buarque em francês por Bïa Krieger [“Portrait en Noir et Blanc”: Chico Buarque en français par Bïa Krieger] - Cassiano, Raissa Conde (Tradução em Revista, 2019)

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.

Auditeurs en exil : le cas des Chiliens à Montréal et leur rapport à deux chansons emblématiques - Gonzalez, Laura Francisca Jordán (Volume !. La revue des musiques populaires, 2013)
Cet article examine l’expérience des auditeurs chiliens exilés à Montréal, se concentrant spécifiquement sur leurs écoutes pendant la dictature militaire (1973-1989). Issus d’une méthodologie mixte qui combine l’histoire orale et l’analyse musicale, les résultats de cette recherche musicologique révèlent la place primordiale que l’audition musicale eut chez les exilés dans la reconstruction d’un lien avec leur pays d’origine, ainsi que dans le développement du mouvement de solidarité avec le peuple chilien. L’article explique, d’abord, le déploiement des goûts musicaux et identifie les répertoires canoniques qui demeurent au centre des écoutes. Ensuite, il aborde le rôle de l’usage des enregistrements en vinyle et cassette, et de la radio dans la diffusion des musiques. Enfin, les deux dernières sections explorent les significations associées aux pièces musicales ‘Gracias a la Vida’ et ‘Vuelvo’, mettant en relief la complexité de la réception en ce qui concerne la construction des identités culturelles, le récit des histoires personnelles et communautaires.
Keywords: bootleg / piratage / contrefaçon; cassette / bande magnétique; communautés / minorités; migration / diaspora / exil; réception; écoute / auditeur

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.

Selanikli Humour in Montreal: the Repertoire of Bouena Sarfatty Garfinkle (1916-1977) - Cohen, Judith R. (Judeo Espaniol: Textos satíricos judeoespañoles: de salonicenses o sobre salonicenses/Satirical Texts in Judeo-Spanish by and about the Jews of Thessaloniki, 2011)

"Si mosós no las vamos a recoger...": The Songbooks of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Los sefardíes ante los retos del mundo contemporáneo. Identidad y mentalidades [Les sépharades face aux défis du monde contemporain. Identité et mentalités], 2010)

Interpreting success and failure: the eclectic careers of Eva and Juliette Gauthier - Slominska, Anita (Université McGill, 2009)
My dissertation explores the eclectic singing careers of sisters Eva and Juliette Gauthier. Born in Ottawa, Eva and Juliettte were aided in their musical aspirations by the patronage of Prime Minister Wilfred Laurier and his wife Lady Zoë. They both received classical vocal training in Europe. Eva spent four years in Java. She studied the local music, which later became incorporated into her concert repertoire in North America. She went on to become a leading interpreter of modern art song. Juliette became a performer of Canadian folk music in Canada, the United States and Europe, aiming to reproduce folk music “realistically” in a concert setting. My dissertation is the result of examining archival materials pertaining to their careers, combined with research into the various social and cultural worlds they traversed. Eva and Juliette’s careers are revealing of a period of transition in the arts and in social experience more generally. These transitions are related to the exploitation of non-Western people, uses of the “folk,” and the emergence of a cultural marketplace that was defined by a mixture of highbrow institutions and mass culture industries. My methodology draws from the sociology of art and cultural history, transposing Eva and Juliette Gauthier against the backdrop of the social, cultural and economic conditions that shaped their career trajectories and made them possible.

Tunes That Bind: Paul J. Seelig, Eva Gauthier, Charles T. Griffes, and the Javanese Other - Spiller, Henry (Journal of the Society for American Music, 2009)
The powerful concept of orientalism has undergone considerable refinement since Edward Said popularized the term with his eponymous book in 1978. Orientalism typically is presented as a totalizing process that creates polar oppositions between a dominating West and a subordinate East. U.S. orientalisms, however, reflect uniquely North American approaches to identity formation that include assimilating characteristics usually associated with the Other. This article explores the complex relationship among three individuals—U.S. composer Charles T. Griffes, Canadian singer Eva Gauthier, and German-trained Dutch East Indies composer Paul J. Seelig—and how they exploited the same Javanese songs to lend legitimacy to their individual artistic projects. A comparison of Griffes's and Seelig's settings of a West Javanese tune (“Kinanti”) provides an especially clear example of how contrasting approaches manifest different orientalisms. Whereas Griffes accompanied the melody with stock orientalist gestures to express his own fascination with the exotic, Seelig used chromatic harmonies and a chorale-like texture to ground the melody in the familiar, translating rather than representing its Otherness. The tunes that bind Griffes, Gauthier, and Seelig are only the raw materials from which they created their own unique orientalisms, each with its own sense of self and its own Javanese others.

Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

A Bosnian Sephardic Woman in Kahnewake, Quebec - Cohen, Judith R. (Canadian Woman Studies/Les cahiers de la femme, 1996)

Women's Roles in Judeo-Spanish Song Traditions - Cohen, Judith R.; Sacks, Maurie (Active Voices: Women in Jewish Culture, 1995)

Sierra norteña: The influence of Latin music on the French-Canadian popular song and dance scene, especially as reflected in the career of Alys Robi and the pedagogy of Maurice Lacasse-Morenoff - Sévigny, Jean-Pierre (Productions Juke-box, 1994)

Expressive Modes in the Judeo-Spanish Wedding Song - Anahory-Librowicz, Oro (New Horizons in Sephardic Studies, 1993)

The Music of the Songs: Musical Transcriptions and Commentary of the Songs Discussed by Oro Anahory-Librowicz "Expressive Modes in the Judeo-Spanish Wedding Song" - Cohen, Judith R. (New Horizons in Sephardic Studies, 1993)

Women and Judeo-Spanish Music - Cohen, Judith R. (Bridge, 1993)

The Odyssey of Dahlia Obadia: Morocco, Israel, Canada - Sawa, Suzanne Myers (Canadian Folk Music Journal, 1991)
Dahlia Obadia interprète les danses de la tradition du moyen orient. Pendant sa carrières, elle a rémarque qu’il existe des grandes différences entre les interprétations de cette tradition vue de l’intérier et de l’extérieur. L’auteur décrit la vie de Dahlia et explore les problèmes qu’elle a affrontes pendant sa quête de sa propre identité culturelle.

"Ya salio de la mar": Judeo-Spanish Wedding Songs among Moroccan Jews in Canada - Cohen, Judith R. (Women and Music in Cross-Cultural Perspective, 1989)